Características fisiológicas, podológicas y somatométricas del jugador profesional de baloncesto - Ramos, D. J.; Rubio, J. A.; Martinez, F.; Jiménez, J. F. (Archivos de medicina del deporte, 2010)
Introduction: A better understanding of the morphofunctional demands of players will help to improve their performance. The position on the court is another important factor, since the movements and physiological demands on each position can change the capabilities of the players. Therefore, the purpose of this study was to analyze the anthropometric, physiological and podiatric characteristics in a professional basketball team. Methodology: There are in this study 24 players of professional basketball league ACB. The sample was divided into 5 groups: Point guard (n1 = 5), shooting guard (n2 = 5), small forward (n3 = 4), power forward (n4 = 4) and center (n5 = 6). Age: 25.4± 4.8 years; Size: 198.2 ± 10.5 cm, Weight: 97.6 ± 14.4 Kg. VO2max 47.9 ± 3.5 ml/Kg/min and maximal hearth rate 180 ± 5 bpm. For the analysis used a Footwork Pro plantar pressures Platform, for anthropometric measures used and an analyzer body composition by bioelectrical impedance (Inbody720). The VO2max test was performed on a Saturn HP Cosmos treadmill with the CPX Ultima gas analyzer and the Well-Challing Cardioperfect ecg. Results: There are significant differences in anthropometric characteristics of different groups in the variables weight, height, muscle mass, cell water, protein, minerals and weight of the limbs. But there are no differences between groups in physiological and plantar pressures variables. Conclusions: Depending on the position occupied by the basketball player in the court there is a characteristic anthropometric profile, however this does not happen in aerobic system or plantar pressures.